System-on-chip next generation electronics - Al-Hashimi, Bashir (Institution of Engineering and Technology, 2006)
System-on-Chip (SoC) is believed to represent the next major market of microelectronics, and there is a considerable interest worldwide in developing efficient methods and tools to support SOC paradigm. The field of SoC is broad and expanding and at present the technical and technological literature about the overall state-of-the-art in SoC is dispersed across a wide spectrum of books. In particular, the book covers the general principles and ideas of designing, validating and testing complex embedded computing systems and their underlying tradeoffs. To enhance the book readability, the chapters are grouped into eight parts, each part examining a particular theme of SoC, including system design, embedded software, power management, reconfigurable computing, network-on-chip, verification and test.